An Analysis of Grade XI Students' Critical Thinking Skills on Animal Tissue Topic in SMA Negeri 1 Kota Mungkid - Fatma, Yunita Nur; Peniati, Endah (Journal of Biology Education, 2020)
These days, critical thinking skills is one of competency that should be developed in students. Critical thinking skills is the ability of a person spotting condition or phenomenon and able to provide judgment according to their prior knowledge. School as an educational organizer has an important role in nurturing and evaluating students critical thinking skills through teaching-learning activity. Critical thinking skills can be developed by using learning methods, learning models, and evaluation in learning activity. This study capturing how the critical thinking skills of Mungkid 1 Public Senior High School 11th grade students in animal tissue topic. This study is a qualitative study with analysis method. Data of this study was taken using observation, interview, test, and questionnaire. The result shows that 53,62% of students belong to low critical thinking skills category due to lacking of variety learning method in the teaching-learning activity (using conventional method instead of variety of models). Also the questions given to the students didn’t support critical thinking skills approach.